A66 GASTRIC HETEROTOPIA OF THE COLON IN A PATIENT WITH A POSITIVE FECAL IMMUNOCHEMICAL TEST. (4th March 2021) - Nassiri, S; Emery, J S; Lee, L H
Abstract: Background: Gastric heterotopia (GH), indicates the presence of ectopic gastric tissue and is a rare entity outside of the small intestine. Abdominal pain and bleeding are described but most colonic GH is found incidentally. Aims: We report a case of colonic GH found on routine screening colonoscopy. Methods: Case report and review of the literature. Results: Case Report: A 60-year-old woman with a history of alcohol use disorder, chronic Hepatitis C, and gastroesophageal reflux disease was referred for colonoscopy after a positive fecal immunochemical test. Remote colonoscopy was notable for a large tubular adenoma with low-grade dysplasia. The patient denied constitutional symptoms, change in bowel habits, or evidence of gastrointestinal (GI) bleeding. No family history of colorectal cancer was reported. Complete blood count, renal function, electrolytes, and carcinoembryonic antigen were normal. At colonoscopy, a 2 cm sessile polyp (0-Is Paris classification) was identified with a normal vascular pattern, but unclassifiable pit pattern. Submucosal injection was suboptimal suggesting tethering. However, given the history of previous polypectomy and favorable endoscopic appearance, piecemeal resection was attempted and achieved fair results. Histology showed abundant pyloric-type glands with overlying foveolar epithelium (Figure 1). Endoscopic follow-up at 8 months confirmed complete resection. Literature Review: GH is observed throughout the GI tract but is predominantly seen in the esophagus and duodenum. Colonic involvement is uncommon with only 12 cases reported. Despite the lack of epidemiological studies, there is a male predominance across all age groups. Pathogenesis is thought to be either congenital, with deposition as the stomach descends during embryogenesis, or acquired secondary to metaplasia following injury to normal intestinal mucosa. Presenting complaints may include altered bowel habits or haematochezia, but most lesions are detected incidentally on surveillance colonoscopy. Endoscopic descriptions are diverse with variations in size (1-60mm), Paris classification (sessile or pedunculated), and appearance (erythematous patch, ulcer, or diverticulum). Endoscopic resection is recommended given association with bleeding but may be technically difficult due to submucosal involvement which may theoretically increase risk of complications such as perforation. Definitive diagnosis rests on histological examination. The risk of malignant transformation of GH in the colon is unknown with only two such cases reported. However, some propose the incidence of malignant change is underestimated as the growing tumor may eliminate the focus of heterotopic gastric mucosa. Conclusions: GH in the colon is a rare entity with diverse endoscopic appearances and poorly understood natural history. Careful endoscopic resection is feasible in the absence of other high-risk endoscopic features. Funding Agencies: None